A relação entre a cultura organizacional e os mecanismos de transferência de tecnologia na Metalúrgica Santa Cecilia S.A. - Pinto, Luiz Alexandre Barbosa (2006)
The aim of this work is to examine the possible relation between organizational culture - previously defined as the set of common organizational meanings. It is also an attempt to understand how cultural values from an organizational group can contribute or influence the choice of technology generator sources. The study is based theoretically and concisely on the conception analysis of the organizational culture, describing its development and maintenance characteristics as well as the elements that compose it. The technical knowledge was theoretically referred to through conceptual approaches, explaining notions of science and technology, bringing about concepts on the transference of technology, its forms of access and detailing its generator sources. Methodologically it is an exploratory, qualitative research, whose technical procedures recommended a case study, which was developed at a metallurgic company in Paraná State, in the mechanic-metal sector. Two distinct instruments for data collection were developed, with the objective of understanding the cultural profile of the organizational group being studied, through investigation of a previously determined set of cultural values and establishing the relation among such cultural values and the technology sources chosen. The results obtained revealed an organizational group (composed by twenty people in position of leadership) with an innovative profile rather than conservative. The relation between their cultural character and the technology sources demonstrated the group’s clear preference for the source of technology represented by internal research and development. The study concludes that the initial hypotheses was confirmed, proving the existence of influence between the culture of the organization and the technology sources chosen. It also points out the strong presence of a certain value or cultural belief, which permeates the results obtained about the cultural profile and about the relation with the technology sources considered. The author also declares his belief that new views on management should try to associate deep knowledge of the organizational reality to the management techniques and elements as a factor of success.